2013
DOI: 10.1161/circinterventions.112.000180
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatory Capacity of the Coronary Microcirculation is Preserved in Selected Patients With Non–ST-Segment–Elevation Myocardial Infarction

Abstract: Background-The use of fractional flow reserve in patients with non-ST-segment-elevation myocardial infarction (NSTEMI) is a controversial issue. We undertook a study to assess the vasodilatory capacity of the coronary microcirculation in patients with NSTEMI when compared with a model of preserved microcirculation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 31 publications
4
88
0
1
Order By: Relevance
“…Use of FFR has been advocated in patients with non-STEMI(37)(38)(39) and FFR can be used to assess stenosis severity of the nonculprit artery in STEMI(16). However, there are no previous data on using FFR in the culprit artery in STEMI.…”
mentioning
confidence: 99%
“…Use of FFR has been advocated in patients with non-STEMI(37)(38)(39) and FFR can be used to assess stenosis severity of the nonculprit artery in STEMI(16). However, there are no previous data on using FFR in the culprit artery in STEMI.…”
mentioning
confidence: 99%
“…11 On the basis of invasive measurement of coronary vasodilator capacity (resistive reserve ratio), we found that patients with stable angina and NSTEMI have a similar vasodilator reserve. 12 Thus, although recent studies are informative, more data concerning the validity of FFR in NSTEMI are needed.…”
Section: Ffr Vs Mri In Nstemimentioning
confidence: 99%
“…This is the basic physiological principle underlying FFR. In ACS, there is potential disruption to the microcirculation from cell death, peri-infarct oedema, microembolic disease and local vasospasm [31]. In this situation there may be a failure to achieve maximal hyperaemia so that pressure measurements will not be proportional to coronary flow and FFR may be inaccurate.…”
Section: Issues In St Segment Elevation Myocardial Infarctionmentioning
confidence: 99%
“…Furthermore, by using a surrogate of a hyperaemic response in 40 patients with acute STEMI, it has been shown that such patients have e28 Coronary Artery Disease 2015, Vol 26 Supplement 1 lowered vasodilatory capacity when compared to stable patients. Intuitively, there was also lower coronary flow reserve and higher index of microvascular resistance in acute STEMI [31]. Thus in patients with acute STEMI the assessment of FFR in the culprit vessel is not recommended.…”
Section: Issues In St Segment Elevation Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation